Analysis on Accounting Conservatism and CSR Disclosures of Indonesian Banks Listed on IDX from 2004 to 2007 - Melissa Kurniawan; Daryanto Hesti Wibowo (Journal of Applied Finance & Accounting, 2009)
Disclosing corporate social responsibility (CSR) activities is mandatory in Indonesia as  regulated by the government. This research investigates whether Indonesian companies are internally motivated to voluntarily conduct their social responsibility agenda.  First, this research examines the conservatism in financial reporting practices of Indonesian banks. It also analyzes the relationship between conservatism and CSR disclosure.  Using 21 Indonesian banks that went public in 2003-2007 as sample, this research conducts a content analysis on their financial reports to measure the conservatism and the CSR disclosure index. The findings of this research reveal that Indonesian banks are, on average, conservative in their financial reporting. This research also provides the ranking of the banks under study in terms of conservatism. Further analysis shows that there is no clear evidence to support the relationship between conservatism and the Indonesian banks’ CSR reporting.  Overall, this research concludes that CSR disclosure practices in Indonesian banks are driven by government regulation. This research does not find any internal motive of the sample banks in disclosing their CSR activities voluntarily.